Squishy Taylor and the Mess Makers - Wild, Ailsa; Wood, Ben, 1983- (Australia : Hardie Grant Egmont, 2016)
Rock-climbing enthusiasts Squishy (real name Sita) and her "bonus" sister Vee (one of a pair of twins), with whom she is currently living, are desparate to meet their heroine, teen climbing sensation Carmeline Clancy, who is staying near them while filming a movie, and they also want to solve a mystery--who is trashing Carmeline's hotel suite and why is she taking the blame?
Primary school
Keywords: Children's stories, English; English fiction